Review of CFTR modulators 2020. Issue 12 (18th August 2021) - Goetz, Danielle M.; Savant, Adrienne P.
Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) modulators are small molecules that directly impact the CFTR protein, improving the function of the CFTR chloride and bicarbonate channel. Beginning in 2012 with the Food and Drug Administration approval of the first CFTR modulator, ivacaftor, this class of medications has had largely positive effects on many outcomes in people with cystic fibrosis (PwCF), including lung function, growth, and other clinical parameters. There have been continued exciting developments in the current research on CFTR modulators, expanding beyond original studies. This first part of a three‐part cystic fibrosis (CF) year in review 2020 will focus on research on CFTR modulators. In addition to reviewing new clinical insights, we describe work done on novel outcomes, adverse effects, issues related to cost, and next steps for clinical trials. The review focuses on articles from Pediatric Pulmonology published in 2020, but it includes articles from other journals that are of particular interest to clinicians. New developments in CF research continue to be brought forth to the CF community, deepening the understanding of this disease and improving clinical care.